Tobacco use in popular movies during the past decade. Issue 4 (24th November 2004) - Mekemson, C; Glik, D; Titus, K; Myerson, A; Shaivitz, A; Ang, A; Mitchell, S
Abstract : Objective: The top 50 commercially successful films released per year from 1991 to 2000 were content coded to assess trends in tobacco use over time and attributes of films predictive of higher smoking rates. Design: This observational study used media content analysis methods to generate data about tobacco use depictions in films studied (n  =  497). Films are the basic unit of analysis. Once films were coded and preliminary analysis completed, outcome data were transformed to approximate multivariate normality before being analysed with general linear models and longitudinal mixed method regression methods. Main outcome measures: Tobacco use per minute of film was the main outcome measure used. Predictor variables include attributes of films and actors. Tobacco use was defined as any cigarette, cigar, and chewing tobacco use as well as the display of smoke and cigarette paraphernalia such as ashtrays, brand names, or logos within frames of films reviewed. Results: Smoking rates in the top films fluctuated yearly over the decade with an overall modest downward trend (p < 0.005), with the exception of R rated films where rates went up. Conclusions: The decrease in smoking rates found in films in the past decade is modest given extensive efforts to educate the entertainment industry on this issue over the past decade. Monitoring, education, advocacy, and policy change to bring tobacco depiction rates down further should continue.